MAX Mutations in Endometrial Cancer: Clinicopathologic Associations and Recurrent MAX p.His28Arg Functional Characterization. (15th November 2017) - Walker, Christopher J; Rush, Craig M; Dama, Paola; O'Hern, Matthew J; Cosgrove, Casey M; Gillespie, Jessica L; Zingarelli, Roman A; Smith, Blair; Stein, Maggie E; Mutch, David G; Shakya, Reena; Chang, Chia-Wen; et al.
Abstract: Background: Genomic studies have revealed that multiple genes are mutated at varying frequency in endometrial cancer (EC); however, the relevance of many of these mutations is poorly understood. An EC-specific recurrent mutation in the MAX transcription factor p.His28Arg was recently discovered. We sought to assess the functional consequences of this hotspot mutation and determine its association with cancer-relevant phenotypes. Methods: MAX was sequenced in 509 endometrioid ECs, and associations between mutation status and clinicopathologic features were assessed. EC cell lines stably expressing MAX H28R were established and used for functional experiments. DNA binding was examined using electrophoretic mobility shift assays and chromatin immunoprecipitation. Transcriptional profiling was performed with microarrays. Murine flank (six to 11 mice per group) and intraperitoneal tumor models were used for in vivo studies. Vascularity of xenografts was assessed by MECA-32 immunohistochemistry. The paracrine pro-angiogenic nature of MAX H28R -expressing EC cells was tested using microfluidic HUVEC sprouting assays and VEGFA enzyme-linked immunosorbent assays. All statistical tests were two-sided. Results: Twenty-two of 509 tumors harbored mutations in MAX, including 12 tumors with the p.His28Arg mutation. Patients with a MAX mutation had statistically significantly reduced recurrence-free survival (hazard ratio = 4.00, 95% confidence interval = 1.15 to 13.91, P = .03). MAX H28R increased affinity for canonical E-box sequences, and MAX H28R -expressing EC cells dramatically altered transcriptional profiles. MAX H28R -derived xenografts statistically significantly increased vascular area compared with MAX WT and empty vector tumors ( P = .003 and P = .008, respectively). MAX H28R -expressing EC cells secreted nearly double the levels of VEGFA compared with MAX WT cells ( P = .03, .005, and .005 at 24, 48, and 72 hours, respectively), and conditioned media from MAX H28R cells increased sprouting when applied to HUVECs. Conclusion: These data highlight the importance of MAX mutations in EC and point to increased vascularity as one mechanism contributing to clinical aggressiveness of EC.